2018
DOI: 10.18272/aci.v10i1.975
|View full text |Cite
|
Sign up to set email alerts
|

La lechuza Campanaria, Tyto alba (Strigiformes: Tytonidae) como regulador de plagas en un ecosistema urbano altoandino en el sur del Ecuador.

Abstract: La progresiva expansión de las urbes no solo implica modificación de los ecosistemas, está también asociada a la introducción de especies plaga. En este sentido, es importante evaluar cómo especies nativas actúan como controladores de plagas. Para asegurar esto, se presenta un análisis de la dieta, basada en egagrópilas, de Tyto alba (Lechuza Campanaria) en la ciudad de Cuenca, Ecuador. En base a 32 egagrópilas, colectadas entre Abril y Junio de 2017, se registró un total de 154 presas asociadas a nueve identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The predominance of rodents in the diet of T. furcata is consistent with studies in other countries [18 and cites therein]. However, this species is also opportunistic, preying upon other kinds of prey, including bats [14] or high number of birds in agricultural and open habitats [18]. Six pellet studies showed the following quantitative data:…”
Section: Tyto Furcatasupporting
confidence: 81%
See 3 more Smart Citations
“…The predominance of rodents in the diet of T. furcata is consistent with studies in other countries [18 and cites therein]. However, this species is also opportunistic, preying upon other kinds of prey, including bats [14] or high number of birds in agricultural and open habitats [18]. Six pellet studies showed the following quantitative data:…”
Section: Tyto Furcatasupporting
confidence: 81%
“…These studies underline the high consumption of rodents [11,12]. This is the best-studied species in Ecuador, most studies being based on pellets analyses, and covering as varied habitats as cities [13,14], rural areas, or agricultural fields in the Pacific lowlands [15][16][17] and Andean valleys [18]. However, there is no long-term research on its diet or a broader study aiming to understand feeding preferences in relation to prey abundance and availability.…”
Section: Tyto Furcatamentioning
confidence: 99%
See 2 more Smart Citations